Omega-3 for the Prevention of Alcohol Use Disorder Relapse: A Placebo-Controlled, Randomized Clinical Trial - Pauluci, Renata; Noto, Ana Regina; Curado, Daniela Fernandez; Siqueira-Campos, Miguel; Bezerra, Andréia Gomes; Galduróz, José Carlos Fernandes (Frontiers in Psychiatry, 2022)
Background: Recent studies have sought to identify the possible benefits of the intake of omega-3, an important component of neuronal membranes, for the treatment of alcohol use disorder. Aim: The objective of the present study was to evaluate whether omega-3 supplementation is protective against alcohol use disorder relapse after hospital discharge. Methods: A placebo-controlled, double-blind, randomized study with inpatients with severe alcohol dependence was conducted. Participants were randomly allocated to treatment with omega-3 (n = 59) or placebo (n = 52) for three months and followed up for 12 months, with evaluations performed using self-report instruments on alcohol consumption, dependence severity and psychiatric symptoms. Results: The groups were similar in regard to consumption amount parameters and propensity to relapse; however, an effect of treatment with omega-3 was found on the number of days of drinking at two months (B = 0.65 [0.09; 1, 21], p = 0.01) and three months (B = 2.6 [1.61; 3.58], p < 0.001) after the start of treatment, favoring the intervention group. The effect was not maintained when the supplement was discontinued. No differences were found in psychiatric symptoms or dependence severity. Conclusions: Our results show that omega-3 can be a therapeutic adjuvant for the treatment of alcohol use disorder after two months of intake and could guide future studies on longer treatment with the supplement. Brazilian Registry of Clinical Trials: nº RBR-48mkgz7 (URL: https://ensaiosclinicos.gov.br/rg/RBR-48mkgz7)